2013
DOI: 10.1080/13572334.2013.811940
|View full text |Cite
|
Sign up to set email alerts
|

MP Transparency, Communication Links and Social Media: A Comparative Assessment of 184 Parliamentary Websites

Abstract: Parliamentary websites (PWs) can potentially enhance the quality of government by providing information and communication links that stimulate political awareness, deliberation and participation. This article focuses on two particular uses of PWs that can facilitate communication between constituents and their Members of Parliament: provision of MP contact and background information; and links to social media. Through a seminal empirical examination of all 184 functioning lower house and unicameral PWs around … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 46 publications
0
24
0
1
Order By: Relevance
“…One important consideration is whether public engagement actually reflects parliament's work, or whether it develops as a parallel activity, both of which depend largely on how these activities are developed and the extent to which they are integrated with parliament's overall work. Whilst a wealth of studies have focused on the features of specific outputs of public engagement, such as new media and petitions (for example, Setälä and Grönlund, 2006;Dai and Norton, 2007;Carman, 2009Carman, , 2010Fox, 2009;Miller, 2009;Joshi and Rosenfield, 2013), we know little about the actual process of implementation of public engagement activities. And yet, the process of implementation can be as important for the suitability of a public engagement output, as it may shape its format and contents.…”
Section: The Implementation Of Public Engagement By Parliamentsmentioning
confidence: 99%
“…One important consideration is whether public engagement actually reflects parliament's work, or whether it develops as a parallel activity, both of which depend largely on how these activities are developed and the extent to which they are integrated with parliament's overall work. Whilst a wealth of studies have focused on the features of specific outputs of public engagement, such as new media and petitions (for example, Setälä and Grönlund, 2006;Dai and Norton, 2007;Carman, 2009Carman, , 2010Fox, 2009;Miller, 2009;Joshi and Rosenfield, 2013), we know little about the actual process of implementation of public engagement activities. And yet, the process of implementation can be as important for the suitability of a public engagement output, as it may shape its format and contents.…”
Section: The Implementation Of Public Engagement By Parliamentsmentioning
confidence: 99%
“…Moreover, the government has an awareness of the need to engage with citizens through social media and start experimenting and exploring the potential of social media (Omar et al, 2014). The high level of social media use found in this study is an indication that there is greater interest in interactive technology, moving beyond the status quo towards greater community involvement (Joshi & Rosenfield, 2013;Leston-Bandeira & Bender, 2013) and the potential for more strategic planning for more sustainable use. Local parliaments must therefore formulate and execute policies to determine why social media is adopted, how interaction is managed, and how resources, time and other conditions are managed.…”
Section: Discussionmentioning
confidence: 72%
“…Online petitions, websites, social media, and other online platforms have been used in recent years by governments and nongovernment actors to encourage citizen engagement and increase the database and overall legitimacy of democracy from the regulation-making process (Joshi & Rosenfield, 2013). The Parliament can take advantage of information crowdsourced, gathering citizen narratives, public consultations and expert knowledge by means of these various media.…”
Section: Parliament In the Digital Eramentioning
confidence: 99%
“…The development of digital mechanisms of engagement and interaction with the public has become a key priority for parliaments throughout the world, as many recent studies and reports have demonstrated (Global Centre for ICT 2012; Griffith & Leston-Bandeira 2012;Inter-Parliamentary Union 2012;Joshi & Rosenfield, 2013). According to the Inter-Parliamentary Union (IPU), the key objectives of the technology experiments currently being made by parliaments around the globe are to amplify the public's understanding about legislatures and to stimulate citizens' participation in the legislative process (IPU 2012, p.21).…”
Section: Parliamentary Websites As a Means To Fulfil New Media's mentioning
confidence: 99%